Nucleation intensification in the ice cream production - Tvorogova, Antonina; Shobanova, Tatyana; Landikhovskaya, Anna; Sitnikova, Polina; Gurskiy, Igor (Eastern-European Journal of Enterprise Technologies, 2020)
In ice cream production, the dispersal of ice crystals ‒ an important organoleptic indicator ‒ depends on the number of water crystallization centers at the first stage of freezing (nucleation). At the subsequent freezing, the remaining water crystallizes at existing centers. This paper reports the results of studying the substantiation of nucleation intensification by increasing the rate of freezing in nitrogen and by employing a germ-forming effect, predetermined by the presence of particles. The nucleation initiators considered are suspended particles of the fat phase and a partially soluble stabilizer (microcrystalline cellulose) and coagulated protein. It has been established that the largest dispersal of ice crystals was achieved when the freezing rate increased while using nitrogen. At a fraction of the frozen water of 40‒50 % under immersion freezing and subsequent aerial pre-freezing the size of ice crystals over 6-month-storage did not exceed 37 µm. It has been shown that the fatty particles were an additional factor in initiating the nucleation at immersion and contact-free freezing in a freezer. We have established a positive effect of the suspended particles of microcrystalline cellulose and coagulated protein on the dispersal of ice crystals in the process of ice cream production and over a 6-month-storage. The average diameter of ice crystals during storage when using microcrystalline cellulose in the creamy ice cream was 39 µm, in fermented milk ice cream containing yogurt – 32‒34 µm. The study results make it possible to define new directions in the intensification of nucleation, based on the principles of the increased rate of freezing and the intensification of nucleation using additional crystallization centers